Harmonic Attenuation of Current and Voltage Using Passive Filters in Residential Electrical Installations - Agung Herdianto (Jurnal Inotera, 2022)
The planning of electrical installation in a residential building needs to be carefully considered because of the variation of load usage, which will lead to the requirement of standard electrical installation. Improper installation will cause a failure in the protection system such as electrical shortage and a reduction in terms of the usage of electrical equipment. In this paper, a harmonic study is conducted on an electrical network that is caused by the non-linear load usage in two-story building with a size of 80 m2. The study is aimed to be one of standards of electrical installation by analyzing harmonic current and voltage as well as its impact to the protection system of residential building. A type of passive filters, that are high pass filter and double tuned filter are applied to dampen the harmonic. The simulation result shows that total harmonic disorder (THD) of non-filter electrical installation has a current harmonic value of 98% and voltage harmonic of 1,3%. On the other hand, there is a significant reduction of harmonic in the electrical installation with a passive filter installed of which the current harmonic value drops to 21%.